The role of NEDD4 related HECT-type E3 ubiquitin ligases in defective autophagy in cancer cells: molecular mechanisms and therapeutic perspectives - Rui Zhang; Shaoqing Shi (Molecular Medicine, 2023)
Abstract The homologous to the E6-AP carboxyl terminus (HECT)-type E3 ubiquitin ligases are the selective executers in the protein ubiquitination, playing a vital role in modulation of the protein function and stability. Evidence shows the regulatory role of HECT-type E3 ligases in various steps of the autophagic process. Autophagy is an intracellular digestive and recycling process that controls the cellular hemostasis. Defective autophagy is involved in tumorigenesis and has been detected in various types of cancer cells. A growing body of findings indicates that HECT-type E3 ligases, in particular members of the neural precursor cell expressed developmentally downregulated protein 4 (NEDD4) including NEDD4-1, NEDD4-L, SMURFs, WWPs, and ITCH, play critical roles in dysregulation or dysfunction of autophagy in cancer cells. The present review focuses on NEDD4 E3 ligases involved in defective autophagy in cancer cells and discusses their autophagic function in different cancer cells as well as substrates and the signaling pathways in which they participate, conferring a basis for the cancer treatment through the modulating of these E3 ligases.